2006
DOI: 10.1308/003588406x82989
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomised, Controlled Trial Comparing Wound Dressings Used in Hip and Knee Surgery: Aquacel and Tegaderm Versus Cutiplast

Abstract: INTRODUCTION Cutiplast (absorbent perforated dressing with adhesive border; Smith & Nephew) is commonly used following orthopaedic operation, but complications of its use have been reported. A prospective, randomised, controlled study was performed to compare the efficacy of Cutiplast versus an Aquacel (hydrofibre dressing; ConvaTec) covered with Tegaderm (vapourpermeable dressing; 3M).PATIENTS AND METHODS Two-hundred patients were randomised to receive one of the two dressings following elective and nonelecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 14 publications
0
62
0
3
Order By: Relevance
“…Only 1 patient required 1 unit of fresh frozen plasma preoperatively for known coagulopathy and cirrhosis. The average incision length was 12.4 cm (range [10][11][12][13][14][15][16]. The average number of Tegaderm films used was 5.3 (range 5-7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 1 patient required 1 unit of fresh frozen plasma preoperatively for known coagulopathy and cirrhosis. The average incision length was 12.4 cm (range [10][11][12][13][14][15][16]. The average number of Tegaderm films used was 5.3 (range 5-7).…”
Section: Resultsmentioning
confidence: 99%
“…The wound exudate is rich in IL-1, PDGF, EGF, and TGF-beta, all of which modulate connective tissue formation and epidermal migration [14]. Winter's research has demonstrated that a moist microenvironment enhances the wound healing process [15]. However, in some instances, some wounds can be highly exudative with persistent leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative peri-wound blistering is a well-recognised phenomenon in orthopaedic surgery (Lawrentschuk et al, 2002;Ravenscroft et al, 2006;Koval et al, 2007;Tustanowski, 2009;Burke et al, 2012). This is because wound dressings are applied over joints that move and cause dressing skin interactions that lead to shear and/or friction episodes and thus blister formation.…”
Section: Can Wound Dressings Cause Blisters and If So How?mentioning
confidence: 99%
“…Thoughts are divided as to whether blisters should be maintained intact or burst (Dearden et al, 2001;Murphy and Amblum, 2014), but blisters associated with wounds have been identified as the main cause for topical wound and skin infections in patients undergoing amputation (Harker, 2006). Some research has identified that the main problems with surgical wounds following hip and knee surgery are blistering and infection, specifically if dressings are applied for a long period (Ravenscroft et al, 2006).…”
Section: What Is the Impact Of Blisters?mentioning
confidence: 99%
See 1 more Smart Citation